Working toward precision medicine approaches to treat severe obesity in adolescents: report of an NIH workshop. Issue 11 (November 2018) - Kelly, Aaron; Marcus, Marsha; Yanovski, Jack; Yanovski, Susan; Osganian, Stavroula
Abstract Adolescent severe obesity is a prevalent, chronic, and serious disease with few effective and safe treatment options. To address this issue, a National Institutes of Health-sponsored workshop entitled "Developing Precision Medicine Approaches to the Treatment of Severe Obesity in Adolescents, " was convened, bringing together a multidisciplinary group of experts to review the current state of the science and identify (1) what is known regarding the epidemiology and biopsychosocial determinants of severe obesity in adolescents, (2) what is known regarding effectiveness of treatments for severe obesity in adolescents and predictors of response, and (3) gaps and opportunities for future research to develop more effective and targeted treatments for adolescents with severe obesity. Major topical areas discussed at the workshop included: appropriate BMI metrics, valid measures of phenotypes and predictors, mechanisms associated with the development of severe obesity, novel treatments informed by biologically and psychosocially plausible mechanisms, biopsychosocial phenotypes predicting treatment response, standardization of outcome measures and results reporting in research, and improving clinical care. Substantial gaps in knowledge were identified regarding the basic behavioral, psychosocial, and biological mechanisms driving the development of severe obesity and the influence of these factors on treatment response. Additional exploratory and observational studies are needed to better understand the heterogeneous etiology of severe obesity and explain the high degree of variability observed with interventions. Tailored treatment strategies that may be developed by achieving a better understanding of individual differences in genetic endowment, clinical, metabolic, psychological, and behavioral phenotypes, and response to environmental exposures need to be tested. It is anticipated that these recommendations for future research, including strategies to enhance methodological rigor, will advance precision medicine approaches to treat severe obesity in adolescents more effectively.